Incidence of Third Head of Biceps Brachii in South Indian Population - Raju Sugavasi,; Indira Devi B,; Madhan Krishna E,; Hima Sarika K,; Krishna Veni S, (Faculty of Medicine, UKM Medical Centre, 2015)
Additional heads of the biceps brachii muscle of arm have the clinical importance, because they mislead the surgeon in arm surgical procedures. Existence of such variation is one of the reasons for neurovascular compression in the arm region. The present study was conducted to find out the incidence of third head of biceps brachii among 80 samples in South Indian population. The third head of biceps brachii was found in right side in one case which was 13.7 cm in length and arising from antero medial wall of lower part of shaft of humerus. Incidence of the study is 1.25% in South Indians. Occurrence of supernumerary third head of biceps is rare in Indian population.